The impact of pedagogical leadership on pedagogical coordination in secondary schools - Inmaculada Garcia Martinez; Pedro Jose Arrifano Tadeu (Research in Social Sciences and Technology- OpenED Network, 2018)
Educational Leadership has an international recognition as a factor in school improvement (OECD, 2009, 2014). The international investigations guarantee this. Within the multiplicity of investigative lines that concern this factor, there is one that alludes to its impact on school improvement, especially in contexts of the social inequality. Within the pedagogical leadership, it has been evidenced that the shared modalities of leadership that invite other members of the educational organization to be involved in a common project are associated with a greater commitment for the improvement and inclusion of all the students. At the same time, other factors come into play, such as the professional identity of both management and staff, professional capital (Hargreaves and Fullan, 2014) or the inclusive practices outlined in this type of context. This intervention oscillates around these issues, offering a vision about studies carried out in the international sphere that associate, on one hand, the impact of leadership on the educational organization and, on the other, positive effects in challenging contexts. Finally, the results obtained from a questionnaire designed specifically for this research will be presented, in which secondary school teachers were asked to respond to questions related to the collaboration in the center, if they received support from the management team to improve their practices if they perceived themselves as school leaders or teachers. Among the results found, it is observed that there is a positive trend towards the construction of a common educational project in secondary schools by the management team. Likewise, there is a positive predisposition on the part of the teaching staff to be more involved in the initiatives of the educational center and towards collaboration and coordination with other colleagues.